Decreased Systemic and Airway Sirtuin 1 Expression in Adults With Bronchiectasis - Han, Xiao-rong; Cen, Lai-jian; Pan, Cui-xia; Lin, Zhen-hong; Li, Hui-min; Zhang, Ri-lan; Huang, Yan; Gao, Yong-hua; Guan, Wei-jie (Frontiers in Medicine, 2022)
Aim: Whether accelerated aging, reflected by sirtuin 1 (SIRT1) expression, is implicated in bronchiectasis remains largely unknown. We sought to determine the patterns of SIRT1 and other aging markers in systemic circulation and airways and their expression levels associated with bronchiectasis severity and exacerbation. Methods: We enrolled 132 patients with bronchiectasis and 50 healthy subjects in a prospective cohort study to profile aging markers in systemic circulation and recruited 36 patients with bronchiectasis and 32 disease controls (idiopathic pulmonary fibrosis or tumors) in a cross-sectional study to profile aging markers in bronchial epithelium of both large-to-medium and small airways. We profiled aging marker expression from peripheral blood mononuclear cells and enumerated the positively stained cells for detection of aging marker expression in bronchial epithelium. Results: Compared with healthy controls, the relative telomere length (median: 0.88 vs. 0.99, p = 0.009), SIRT1 (median: 0.89 vs. 0.99, p = 0.002), and Ku80 (median: 0.87 vs. 0.96, p < 0.001) expression levels were consistently lower in the peripheral blood mononuclear cells among patients with bronchiectasis and modestly discriminated patients with bronchiectasis from healthy controls. No remarkable changes in SIRT1, telomere length, or Ku70 were identified at onset of exacerbation. Within the bronchial epithelium, the percentage of positively stained cells was lower for SIRT1 (median: 25.1 vs. 57.2%, p < 0.05) and numerically lower for p16 (median: 40.0 vs. 45.1%) and p21 (median: 28.9 vs. 35.9%) in patients with bronchiectasis than in disease controls (p > 0.05). Conclusion: SIRT1 was downregulated in systemic circulation and bronchiectatic airways, which was independent of disease severity and lung function impairment.